People with newly diagnosed multiple sclerosis benefit from a complex preventative intervention-a single group prospective study with follow up - Hrušková, Natália; Berchová Bímová, Kateřina; Davies Smith, Angela; Škodová, Tereza; Bičíková, Marie; Kolátorová, Lucie; Štětkářová, Ivana; Brožek, Ľuba; Javůrková, Alena; Angelová, Gabriela; Řasová, Kamila (Frontiers in neurology, 2024)
BACKGROUND: Newly diagnosed people with multiple sclerosis frequently report fatigue, pain, depression and anxiety. Preventative programmes may be beneficial, but there is limited evidence of their effectiveness, especially long-term follow-up. METHODS: The programme consisted of 6-month face to face intervention (an introductory workshop, psychology-led group sessions and individual physical therapy) followed by 6-month self-guided therapy. Outcome measures were taken at baseline, 6 and 12 months. Primary outcomes measures were self-report questionnaires for fatigue, satisfaction with life and disease acceptance. Secondary outcomes were spirometry, spiroergometric parameters and neuroactive steroid levels. RESULTS: From 22 participants enrolled, 17 completed the first 6 months and 13 the follow-up. Fatigue measured on the Fatigue scale for motor and cognitive functions decreased significantly at 6 months (p = 0.035) and at follow-up (p = 0.007). The Modified Fatigue Impact Scale (p = 0.035) and Satisfaction With Life Scale (p = 0.007) significantly increased at follow-up. Spirometry, spiroergometric parameters, steroid hormones and neuroactive steroids levels did not change significantly. CONCLUSION: This programme reduces fatigue and improves satisfaction with life in this patient group with improvements sustained at 12 months. People who participated more frequently showed greater benefit. CLINICAL REHABILITATION IMPACT: The paper describes the effects of a complex preventative intervention for people with newly diagnosed Multiple Sclerosis. The study found that this programme reduces fatigue and improves satisfaction with life with long-term benefit (at 12-month follow up). The individuals who participated less frequently experienced fewer benefits.
Keywords: cognitive behavioural therapy; multiple sclerosis; aerobic training; neuroactive steroids; fatigue; satisfaction with life; physical therapy